Development and implementation of a TaqMan triplex real-time PCR assay for concurrent detection of pseudorabies virus, porcine teschovirus 1, and Streptococcus suis 2 - Lai, Ranran; Yang, Chen; Wu, Lili; Wu, Weisheng; Li, Lulu; Liu, Wei; Yan, Zheng; Yu, Diankun; Ren, Shengzhi; Hu, Zhiqiang; Li, Xiaowen (Frontiers in Veterinary Science, 2025)
IntroductionPorcine neurological disorders represent a prevalent clinical condition that leads to significant mortality and economic losses within the swine industry. Pseudorabies virus (PRV), porcine teschovirus 1 (PTV1), and Streptococcus suis 2 (SS2) are key viral and bacterial pathogens implicated in the manifestation of neurological symptoms in pig populations. The overlapping clinical presentations and pathological alterations associated with these pathogens pose challenges in their clinical differentiation. Therefore, it is essential to develop a diagnostic method with high sensitivity and specificity that can simultaneously detect and differentiate these viral and bacterial agents.Materials and methodsA triplex real-time PCR assay using TaqMan probes was developed to simultaneously detect PRV, PTV1, and SS2. To assess the efficacy of the established assay, 30 clinical samples of animals with nervous symptoms were used to compare the results obtained from the triplex real-time PCR assay with those obtained from commercial singleplex real-time PCR kits. Furthermore, a total of 282 samples were tested and analyzed to validate the utility of the assay.ResultsThe triplex real-time PCR assay exhibited high sensitivity, specificity, and repeatability, with a detection limit of 1.0 × 100 copy/μL. The triplex real-time PCR method and commercial singleplex real-time PCR kits showed complete concordance in detecting PRV, PTV1, and SS2. Clinical data indicated single infection rates of 8.16% for PRV, 26.95% for PTV1, and 7.80% for SS2. The observed co-infection rates were 7.45% for PRV + PTV1, 0.71% for PRV + SS2, 1.42% for PTV1 + SS2, and 1.77% for PRV + PTV1 + SS2, respectively.ConclusionThe triplex real-time PCR method developed in this study effectively distinguishes PRV, PTV1, and SS2 simultaneously, serving as a valuable diagnostic tool. This method is anticipated to play a crucial role in preventing and controlling infectious disease spread and supporting epidemiological investigations.